Near-Infrared Spectroscopy (NIRS)-based Digit Skin Tissue Blood Flow Measurement System - Yin, Tan Ying; Mahmud, Farhanahani; Ramli, Nur Ilyani (International Journal of Engineering and Technology, 2018)
The tissue blood flow (BF) and vascular resistance are the important information for consult peripheral vascular system which related to cardiovascular disease. Unfortunately, most of the current BF monitors are costly, built in huge size and preferable use in hospital and clinic. In the present study, a portable digit skin tissue BF measurement system had been developed using Near-infrared spectroscopy (NIRS) method with simple circuitry and low cost that can be afforded by patients to monitor their cardiovascular information. This system consists of a self-developed NIRS probe; LED and a photodiode, and an Arduino Uno board with MATLAB software as the processing unit. The NIR LED transmits 810 nm light source through biological tissue then detected by the photodiode. The output signal from the NIRS probe is based on resistance changes in the photodiode and by applying the voltage divider law, the signal is further processed by the Arduino with the MATLAB software. Then, according to the modified Lambert-Beer Law in scattering medium, the change in total concentration of haemoglobin ( ) is plotted in order to get a quantitative BF reading which based on its maximum change during venous occlusion. To evaluate the proposed BF measurement system, BF measurement tests had been conducted on four healthy subjects during resting and after exercise. The study had shown that the results of BF after the exercise were in average of 1.5 time higher than the resting BF and this finding agrees with previous research works.